The Effect Of Financial Attitude, Financial Literacy And Family Financial Education On Financial Management Behavior Of E-Wallet Users In Financial Self Efficacy Mediation: Pengaruh Sikap Keuangan, Literasi Keuangan dan Pendidikan Keuangan Keluarga terhadap Perilaku Pengelolaan Keuangan Pengguna E-Wallet Di Mediasi Efikasi Diri Keuangan - Yoga Widodo, Kurniawan; Sutrisno; Rita Meiriyanti (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This research aims to determine the Influence of Financial Attitude, Financial Literacy and Family Financial Education on the Financial Management Behavior of E-Wallet Users in the Mediation of Financial Self-Efficacy. The method used in this study is a quantitative method, using primary data with a data collection method using a questionnaire. Hypothesis testing uses the Structural Equation Model (SEM) method with the help of SmartPLS software. The results of this study prove that: (1) financial attitude does not affect the financial self-efficacy of e-wallet users (2) financial literacy has a positive effect on the financial self-efficacy of e-wallet users (3) family financial education affects the financial self-efficacy of e-wallet users (4) financial attitude does not affect the financial management behavior of e-wallet users. (5) financial literacy does not influence the financial management behavior of e-wallet users (6) family financial education has a positive influence on the financial management behavior of e-wallet users (7) financial self-efficacy influences the financial management behavior of e-wallet users (8) states that financial attitude does not influence financial management behavior through the financial self-efficacy of e-wallet users (9) financial literacy influences financial management behavior through the financial self-efficacy of e-wallet users (10) family financial education influences financial management behavior through the financial self-efficacy of e-wallet users.